Alleppey Tourism Development Cooperative:The Case of Network Advantage - Babu P George (The Innovation Journal: The Public Sector Innovation Journal, Volume 12(2), 2007, 2007)
This case study portrays an important organizational innovation in the SME sector of the tourism industry. ATDC is a cooperative society of houseboat owners and other stakeholders in the houseboat tourism business in Alleppy, a backwater town located in the southern State of Kerala, India. The study describes the genesis and growth of houseboat tourism in Alleppey which is intertwined with the history of ATDC. Cooperativism is hardly ever mentioned in the tourism literature as one of the formidable options for business organization and only scarcely observed in the world of tourism practice. However, in the case of ATDC, the cooperative experimentation was inevitable given the chemistry of unique economic and socio-cultural circumstances surrounding the small-scale boat owners. The case of ATDC is a revelation of the otherwise unnoticed benefits of cooperative alliances in an industry like tourism: the provision of truly authentic products to the tourists; the opportunity for mass-customization; and the concern of the alliance members for sustainable development of the region. Also uncovered from the case study are the vital characteristics of a cooperative entrepreneur.